E0102 Expression or secretion of IL-34 and IL-35 in the peripheral blood mononuclear cells from patients with dilated cardiomyopathy. (17th November 2010) - Sisi, Huang; Weifeng, Wu; Song, Lin; Yanlan, Huang
Abstract : Objective: The aim of this study was to observe the level of interleukin (IL)-34 and IL-35 in peripheral blood mononuclear cells (PBMCs) with dilated cardiomyopathy (DCM), and explore the role of IL-34 and IL-35 in human DCM. Methods: 30 patients with DCM and 30 normal adults as control were studied. IL-34 and the subunit Epstein-Barr virus-induced gene 3(EBI3) of IL-35 mRNA expression in PBMCs were detected by reverse transcription–PCR (RT-PCR). IL-34 and IL-35 protein level in plasma were measured with ELISA. Result: (1) Results showed that the IL-34 mRNA level or its protein level was significantly elevated in DCM patients compared with normal control subjects. (mRNA level: DCM :0.37±0.08, NC: 0.19±0.03, p<0.01; protein level: DCM: 208.94±50.31 pg/ml; NC: 175.69±44.56 pg/ml; p<0.01) (2) The IL-35 subuint-EBI3 or its protein level was significantly decreased in DCM patients compared with normal control subjects. (EBI3 mRNA level: DCM: 0.15±0.03, NC: 0.33±0.07, p <0.01; protein level: DCM: 128.68±24.08 pg/ml, NC: 179.73±43.89 pg/ml, p<0.01) (3) The secretion of IL-34 was markedly correlation with the secretion of IL-35 (r=−0.490, p <0.01). (4) The protein level of IL-34 in DCM patients had a positive correlation with heart function (r=0.598, P <0.01). (5) The protein level of IL-35 in DCM patients had a negative correlation with heart function (r=−0.839, p<0.01). Conclusion: The ability to express IL-34 and IL-35 protein or mRNA in PBMCs is abnormal and the change strongly correlates with ejection fraction and heart function of DCM patients.